2006
DOI: 10.1017/s1461145706007127
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of repetitive transcranial magnetic stimulation and electroconvulsive therapy in unipolar non-psychotic refractory depression: a randomized, single-blind study

Abstract: Repetitive transcranial magnetic stimulation (rTMS) can induce significant antidepressant effects and, for some patients, might be an alternative to electroconvulsive therapy (ECT). The results of studies comparing the efficacy of rTMS and ECT are mixed and, therefore, comparison of these two therapies needs to be further explored. Forty-two patients aged between 18 and 65 yr, referred to ECT due to unipolar non-psychotic depression refractoriness entered the trial. They were randomly assigned to receive eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 31 publications
0
33
0
6
Order By: Relevance
“…Similarly, Rosa et al [42] suggested that there was no difference in terms of neuropsychological test performance between 42 TRD patients aged between 18 and 65 years who were randomly assigned to receive either rTMS or ECT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rosa et al [42] suggested that there was no difference in terms of neuropsychological test performance between 42 TRD patients aged between 18 and 65 years who were randomly assigned to receive either rTMS or ECT.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the main findings, most (16) of the selected studies [23,25,28,37,38,39,40,43,45,46,47,48,49,50,51,54] supported the association between rTMS and neurocognitive effects; only two studies [52,53] suggested the existence of a trend towards improvements in neurocognitive profile using rTMS, and some (4) studies [36,41,42,44] did not confirm this association (tables 1, 2, 3). …”
Section: Discussionmentioning
confidence: 99%
“…However, many studies failed to demonstrate significant cognitive effects [24,25,26,27,28,29,30], but they could show trends toward selective cognitive improvements. Studies using 1-Hz stimulation are limited because of methodological differences (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A metodologia de localização da bobina sobre a região do CPM/CPFDL esquerdo empregado no presente estudo é a mesma utilizada na maioria das pesquisas sobre a EMTr na depressão (PascualLeone et al, 1996;George et al, 2000;Fitzgerald et al, 2002;Rumi et al, 2005;Rosa et al, 2006) (Eisendrath, 1995;Gallagher;Verma, 2004) ou com AVC (Herrmann et al, 1995;Hackett;Anderson, 2005;Loubinoux et al, 2012). A EMTr com frequência superior a 5 Hz do CPFDL esquerdo modula intensamente os circuitos fronto-cingulados envolvidos no controle do humor (Paus et al, 2001) e tem papel estabelecido na terapêutica de doentes com transtornos depressivos (Rumi et al, 2005;O´Reardon et al, 2007;George et al, 2010).…”
Section: Discussionunclassified